2019
DOI: 10.1111/phn.12657
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Intervention Wheel in Norway

Abstract: Objective This study explored experiences Norwegian public health nurses (PHNs) have with using interventions from the Public Health Intervention Wheel (PHIW). Design and Sample The researchers used both quantitative and qualitative measures to explore how Norwegian PHNs use PHIW interventions in their practice. Data were gathered from six focus group meetings with 15 school and 16 family health nurses in Norway. Method Instruments included: (a) demographic data form, (b) the Public Health Intervention Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…The importance of infection control was highlighted during the recent COVID-19 pandemic (Ministry ofHealth and Care Services, 2020). Norwegian PHNs use interventions like surveillance, disease and health event investigation, outreach, screening, and case finding in their work(Glavin et al, 2019).PHNs' ethical competence is prominent in our findings, and this is in line with the competence in non-judgmental acceptance of others found in the literature. For example,Glavin et al (2014) compared the values and beliefs of Norwegian public health nursing with the values and beliefs reflected in cornerstones of U.S. public health nursing and found many similarities.Permeating our findings was the PHNs' holistic thinking: This dovetails with the competence area we identified in the literature, which described a holistic understanding of health at all levels of public health nursing work Fukada (2018).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The importance of infection control was highlighted during the recent COVID-19 pandemic (Ministry ofHealth and Care Services, 2020). Norwegian PHNs use interventions like surveillance, disease and health event investigation, outreach, screening, and case finding in their work(Glavin et al, 2019).PHNs' ethical competence is prominent in our findings, and this is in line with the competence in non-judgmental acceptance of others found in the literature. For example,Glavin et al (2014) compared the values and beliefs of Norwegian public health nursing with the values and beliefs reflected in cornerstones of U.S. public health nursing and found many similarities.Permeating our findings was the PHNs' holistic thinking: This dovetails with the competence area we identified in the literature, which described a holistic understanding of health at all levels of public health nursing work Fukada (2018).…”
supporting
confidence: 88%
“…Using the PHIW as a framework for PHNs' practice thus provides a common language with which to describe their practice; this, in turn, enables the justification of necessary resources for the work to funding authorities (Minnesota Department of Health, 2019). The PHIW framework is found applicable to a Norwegian setting (Glavin et al, 2019). As such, Norwegian standards for the actions and role of PHNs must be clear to users, management, partners and the PHNs themselves.…”
Section: Public Health Nurses' Professional Practice Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers publish the processes they use to develop interventions to improve healthcare to help future developers to improve their approaches, plans and practices. Description of the development of interventions is important because it provides future developers with the terminology and language to identify, conceptualise and explain their rationales and more effectively plan and design context-specific intervention models [ 43 ]. It is important to understand how the models that end up being designed during interventions, complement the traditional ways of doing things for the betterment of a common good such as public health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they conducted a qualitative study to explore how Norwegian PHNs used Wheel interventions. Although there are structural differences in public health services between Norway and the United States, PHNs in the study indicated the Wheel was applicable to their practice and gave them a language to describe their work (Glavin et al., 2019).…”
Section: The Wheel In Cultural and International Public Health Nursingmentioning
confidence: 99%